Orientasi matlamat dan kebimbangan pra pertandingan di kalangan atlet hoki bawah 18 tahun / Rosli Saadan - Rosli , Saadan (2016)
The purpose of this research was to identify differences between goal orientation and pre-competition anxiety among under 18 hockey athletes. In addition, the differences of the level of goal orientation and pre-competition anxiety between groups were also analyzed. This study employed a quasi-experimental approach. 144 participants were selected as sample for this study. This study involved four groups in which three groups were experimental groups and one group was the control group. There were 36 respondents in each group. Experimental groups were given intervention before, while and after training session, while the control group was not given any intervention. Data were collected twice ; immediately before the training and an hour before the competition using Task and Ego Orientation in Sport Questionnaire (TEOSQ; Duda & Nicholls, 1992) and Revised Competitive State Anxiety Inventory-2 (CSAI-2R; Cox et al., 2003) survey. MANOVA analysis showed that there was significant difference between genders and dependent variables. This could be clearly seen from the values of Pillai’s trace = 0.260 and F value [(10, 127) = 4.453, p < 0.05]. Findings also showed that there were significant difference among groups in all the dependent variables as the value of Pillai’s trace = 0.527 and F value [(30, 387) = 2.746, p < 0.05]. Findings also showed that there were interaction between variables when the value of Pillai’s trace = 0.614 and F value [(30, 387) = 3.319, p < 0.05]. Findings also showed that there were significant difference between gender for pre-test orientation subscale [F (1,136) = 10.84, p < 0.05], pre-test ego orientation [F (1,136) = 9.117, p < 0.05], pre-test cognitive anxiety [F (1,136) = 16.23, p < 0.05] and post-test self-confidence [F (1,136) = 3.983, p < 0.05]. Post-hoc analysis comparison between groups revealed a significant difference between Task & Ego group and Ego group [F (3,136) = 0.010, p < 0.05], Task & Ego and Control group [F (3,136) = 0.006, p < 0.05]. For post-test task orientation subscale, there was significant difference between Task & Ego group and Task group [F (3,136) = 0.008, p < 0.05], Task group and Ego group [F (3,136) = 0.003, p < 0.05] and Task group and Control group [F (3,136) = 0.002, p < 0.05]. For pre-test ego orientation subscale, there was significant difference between Task & Ego group and Task group [F (3,136) = 0.001, p < 0.05], Task & Ego group and Ego group [F (3,136) = 0.038, p < 0.05]; Task & Ego group and Control group [F (3,136) = 0.001, p < 0.05] and Ego group and Control group [F (3,136) = 0.035, p < 0.05]. On the other hand, for post-test ego orientation subscale, there was significant difference between Task & Ego group and Task group [F (3,136) = 0.013, p < 0.05].